2019
DOI: 10.32890/jict2019.18.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Network of Traffic Accidents in Malaysia

Abstract: Exploring the causes and effects of a hazardous event such as traffic accidents have been of vital importance to society. Statistical analyses have been widely implemented to understand and deduce inferences on the cause-effect analysis, and to anticipate the occurrences of accidents in the future. One of the issues that has not been solved through conventional statistical modelling is the existence of interrelationships between variables in the data set. However, with the advent of technology and the wide app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…BBN has been applied to analyze traffic accidents in different countries. For example, Zou and Yue [47] studied accident causation in Australia, Karimnezhad and Moradi [48] studied the causes of accidents in Iran, Deublein et al [49] studied the causes of accidents in Switzerland, and Zamzuri et al [50] studied the causes of accidents in Malaysia. However, to the authors' knowledge, no BBN model has been proposed for road safety modeling in Saudi Arabia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…BBN has been applied to analyze traffic accidents in different countries. For example, Zou and Yue [47] studied accident causation in Australia, Karimnezhad and Moradi [48] studied the causes of accidents in Iran, Deublein et al [49] studied the causes of accidents in Switzerland, and Zamzuri et al [50] studied the causes of accidents in Malaysia. However, to the authors' knowledge, no BBN model has been proposed for road safety modeling in Saudi Arabia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Keay and Simmonds 17 designed a regression model for the effect of weather on tra c; Yu 18 established a highway collision model using Poisson model and Bayesian inference method. Selvaso a and Arulraj 19 used GIS for tra c accident analysis; Zamzuri 20 used Bayesian network and HC algorithm and Tabu algorithm to explore the causes of tra c accidents in Malaysia; Zhang 21 used text processing technology based on LDA Topic Model to analyze tra c accidents to obtain the most dominant factors of tra c accidents; Deng 22 proposed a causality analysis model for tra c accidents using a hybrid AHP and Apriori-Gentic based algorithm to mine accident causes. Bayesian network is a good way to model causality, and Bayesian network can effectively form probabilistic models for e cient inference and learning 23 .…”
Section: Introductionmentioning
confidence: 99%
“…A study done by Zamzuri et al (2019) identified accident variables such as weather, light condition, traffic system, lane marking, road geometry, collision type and accident severity when investigating the interrelationship between these variables to further understand the cause of accidents. Furthermore, many studies reported on the causes or factors that are closely related to accident severity specifically on accidents occurrence and their locations.…”
Section: Introductionmentioning
confidence: 99%